Leadership Take Charge of Your Team: Coach, Motivate and Inspire - Alan Anderson (Independently Published Alan Anderson, 2020)
With technological advancements and globalization changing the way that businesses operate, it follows that organizational management must adapt to meet the needs of the times, and this calls for the evolution of leadership.
Keywords: Leadership